Neuro-hormonal effects of physical activity in the elderly - Femminella, Grazia Daniela; De Lucia, Claudio; Iacotucci, Paola; Formisano, Roberto; Petraglia, Laura; Allocca, Elena; Ratto, Enza; D'Amico, Loreta; Rengo, Carlo; Pagano, Gennaro; Bonaduce, Domenico; Rengo, Giuseppe; et al. (Frontiers in Physiology, 2013)
Thanks to diagnostic and therapeutic advances, the elderly population is continuously increasing in the western countries. Accordingly, the prevalence of most chronic age-related diseases will increase considerably in the next decades, thus it will be necessary to implement effective preventive measures to face this epidemiological challenge. Among those, physical activity exerts a crucial role, since it has been proven to reduce the risk of cardiovascular diseases, diabetes, obesity, cognitive impairment and cancer. The favourable effects of exercise on cardiovascular homeostasis can be at least in part ascribed to the modulation of the neuro-hormonal systems implicated in cardiovascular pathophysiology. In the elderly, exercise has been shown to affect catecholamine secretion and biosynthesis, to positively modulate the renin-angiotensin-aldosterone system and to reduce the levels of plasma brain natriuretic peptides. Moreover, drugs modulating the neuro-hormonal systems may favourably affect physical capacity in the elderly. Thus, efforts should be made to actually make physical activity become part of the therapeutic tools in the elderly.